Energy model for optically controlled MESFETs - Al-Sunaidi, M. A. (2000)
An energy-based transport model for the analysis of illuminated microwave active devices is presented. The model is based on the Boltzmann's transport equation, with optical carrier generation and carrier recombination accounted for. The simulation results are compared with the conventional local-field mobility models based on drift-diffusion formulations. It is shown that the drift-diffusion models lose their applicability in submicrometer gate-length devices. The presented time-domain model has a great potential in the analysis of microwave devices under ac and pulsed illumination conditions.